Patient reported outcome measures (PROMs) in breast cancer patients after immediate breast reconstruction using the Breast-Q - Möller, Ernst Lodewicus (Division of Plastic and Reconstructive Surgery, 2021)
Background Mastectomy is the mainstay of surgical treatment for women with breast cancer in South Africa. The increase in breast reconstruction after a mastectomy has prompted the need to evaluate patient reported outcome measures (PROMs) for this set of operative intervention. This study aimed to assess clinical and patient reported outcome measures in immediate breast reconstruction patients using the BREAST-Q and compare these with international cohorts. Methods A cross-sectional study was performed on all patients who underwent immediate breast reconstruction between January 2011 and December 2016. This consisted of a retrospective clinical record review of perioperative outcomes, and a quality of life analysis using the BREAST-Q Post-Reconstruction questionnaire. Outcome predictors were identified using Chi-square, Fisher exact, One-way ANOVA, Student t-tests and Kruskal Wallis analysis of variance. A random-effect single arm meta-analysis was performed to compare the BREASTQ scores with international cohorts. Results A total of 52 patients were included with a mean age of 43.2 (+/-9.5) years. Eighteen patients (34.6%) developed early complications; of these 8 (44.4%) were major. Thirty-one patients (59.6%) developed late complications; of these 18 (58.1%) were major. Fifteen patients (28.8%) had failed reconstruction. There was a significantly higher risk of failure following a total mastectomy (TM) (p=0.02), tissue expander reconstruction (TE) (p< 0.01) and stage 2 breast cancer (p=0.01). Patients who underwent nipple reconstruction and immediate-delayed reconstruction before 12 months, reported higher well-being and satisfaction scores. Compared to international cohorts our BREAST-Q scores were lower but fall within the 95% confidence interval for Sexual Well-Being and Satisfaction with Nipples and Care. Conclusion Immediate breast reconstruction poses a high risk of complications and reconstructive failure especially, with TM and TE. Our BREAST-Q scores are comparable to international studies and may be useful in guiding patient consent.